2023
DOI: 10.1039/d2me00179a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative degradation of sequence-defined peptoid oligomers

Abstract: Due to their N-substitution, peptoids are generally regarded as resistant to biological degradation, such as enzymatic and hydrolytic mechanisms. This stability is an especially attractive feature for therapeutic development and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…[7][8][9] These polymeric antibacterial agents, such as polyacrylates, 10 polynorbornenes, 11 and polypeptides, 12 offer significant improvements over natural AMPs, including superior stability, ease of synthesis, and low cost. [13][14][15][16][17] Polypeptoids with a degradable backbone, 18 also known as N-substituted glycines, represent one of the most important peptide analogues and show great potential in various biomedical applications. 19 The highly tunable structure of polypeptoids means that they retain the backbone structure of the polypeptide and lose the chiral center and hydrogen bond, thus providing better biocompatibility and protein bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] These polymeric antibacterial agents, such as polyacrylates, 10 polynorbornenes, 11 and polypeptides, 12 offer significant improvements over natural AMPs, including superior stability, ease of synthesis, and low cost. [13][14][15][16][17] Polypeptoids with a degradable backbone, 18 also known as N-substituted glycines, represent one of the most important peptide analogues and show great potential in various biomedical applications. 19 The highly tunable structure of polypeptoids means that they retain the backbone structure of the polypeptide and lose the chiral center and hydrogen bond, thus providing better biocompatibility and protein bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Since peptoid secondary structures are strongly dependent on steric interactions, their native backbone configurations are resistant to changes in external conditions such as temperature and pH. , Peptoid secondary structures are fundamentally different from those of peptides, with the major minima being displaced by 180° with respect to the ϕ and ψ dihedral angles mentioned above, as shown in Figure . For this reason, peptoids are also resistant to protease action as they do not fit into protease-binding pockets, which are usually tuned specifically to peptides. , The folding properties and the secondary structure expressed by a peptoid polymer can be controlled by altering the conditions during manufacturing. ,,, Experiments have also shown that peptoids have enhanced cellular uptake properties while maintaining reduced immune responses, unlike most peptidomimetics. , All of these features make peptoid attractive candidates for investigation using both experimental and computational means.…”
Section: Introductionmentioning
confidence: 99%
“…Peptoids [32], N-substituted glycine oligomers, have gained significant attention in recent years due to their potential applications in various biological processes, including protein interactions [33][34][35] metal binding [36,37], and catalysis [38][39][40][41]. This increased interest is due to the following advantages: (i) their efficient synthesis on a solid support via the "sub-monomer" method [42], which employs primary amines instead of amino acids, eliminating multiple protection/deprotection steps and allowing for the incorporation of different functional side chains, including metal-binding ligands (MBLs); (ii) their ability to adopt well-defined secondary structures when specific bulky-chiral side chains are introduced into their sequences [43][44][45][46][47]; (iii) their good bioavailability being resistant to proteases [48,49], having high membrane permeability [50,51] and tolerance to various conditions such as high temperatures [52], salt concentrations and pH levels [53,54]. Over the past decade, our group has extensively studied peptoids for copper-targeting chelation [43].…”
Section: Introductionmentioning
confidence: 99%